EDUCAÇÃO AMBIENTAL E OS SISTEMAS DE GESTÃO AMBIENTAL NO DESAFIO DO DESENVOLVIMENTO SUSTENTÁVEL - Alcântara, Larissa Azambuja; Silva, Maria Clara Araújo; Nishijima, Toshio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704198 Currently, Environmental Education has assumed a growing importance in society. Through theinclusion of sustainable development and educational practices for the conservation of theenvironment we seek to better quality of life for society, where it should be kept in balance withthe ecosystem. This work is justified conceptually by considering the interaction between twofundamental aspects for the sustainability and balance of the ecosystem, together with theEnvironmental Education Environmental Management. Environmental education should beapproached in a systematic and cross at all levels of education, ensuring the presence of theenvironmental dimension of interdisciplinary curricula. This practice provides the change of valuesand skills upgrading, conditions necessary to obtain a balance between the citizens and the naturalenvironment. Thus, environmental education can be seen as a socio-educational practiceintegrated, continuous and permanent, in order to inform, sensitize and compromising society andpolicy makers on the importance of understanding and reduce environmental problems. Togetherwith the Environmental Education, Environmental Management Systems has gained an increasingspace in the business. Increased environmental awareness is visible at different levels and sectorsof society. Thus, the application of Environmental Management aims to create techniques, plan,organize and manage economic and social activities in order to rationally use natural resources aswell as carry out compliance with environmental legislation. Presents multidisciplinary thereforeprofessionals from diverse fields can act in the area, if properly enabled. Thus, there is therelationship between Environmental Education and Environmental Management, therefore, actingalongside these instruments become essential to maintain the balance between the environmentand society. It is not enough to count on efficient management systems and, yes putenvironmental education as a starting point for further technical and seek solutions for the benefitof the natural environment. Thus, the Environmental Education acting as an instrument ofenvironmental management can become effective and efficient by changing the values, conceptsand behaviors. And, combined with other instruments of economic control is contributing to theconstruction of a self-sustainable, prioritizing the environmental balance.